Chemistry of bioconjugates : synthesis, characterization, and biomedical applications - Narain, Ravin (Hoboken, New Jersey : Wiley, 2014)
This book describes the chemistries involved in bioconjugation followed by an extensive review of all types of bioconjugates (polymers, dendrimers, nanoparticles, carbon nanotubes) reported in the literature for different bio-related applications. A section is devoted to the physico-chemical and biochemical properties of bioconjugates and implications in their uses. Finally, the book also provides a comprehensive account about the significance of bioconjugation - coverage that is lacking in many of the current resources available.
General methods of bioconjugation -- Covalent and noncovalent bioconjugation strategies -- Polymer bioconjugates -- Bioconjugates based on poly(ethylene glycol)s and polyglycerols -- Synthetic polymer bioconjugate systems -- Natural polymer bioconjugate systems -- Dendrimer bioconjugates: synthesis and applications -- Organic nanoparticles based bioconjugates -- Bioconjugation strategies: lipids, liposomes, polymersomes, and microbubbles -- Organic nanoparticle bioconjugate: micelles, cross-linked micelles, and nanogels -- Carbon nanotubes and fullerene C60 bioconjugates -- Inorganic nanomaterials bioconjugates (metals, metal oxides--quantum dots, iron-oxide) -- Gold nanomaterials bioconjugates -- Methods for magnetic nanoparticle synthesis and functionalization -- Quantum dots bioconjugates -- Silica nanoparticle bioconjugates -- Polyhedral oligomeric silsesquioxanes (POSS) bioconjugates -- Cell-based, hydrogels/microgels and glyco-bioconjugates -- Cell-based bioconjugates -- Bioresponsive hydrogels and microgels -- Conjugation strategies used for the preparation of carbohydrate-conjugate vaccines -- Characterization, physico-(bio)chemical properties, and applications of bioconjugates -- Properties and characterization of bioconjugates -- Physico-chemical and biochemical properties of bioconjugates -- Applications of bioconjugates.
Description based on print version record and CIP data provided by publisher.
Includes bibliographical references and index.
Keywords: Bioconjugates; Biopolymers -- physiology; Nanostructures -- chemistry; Chemistry Techniques, Synthetic; MEDICAL -- Physiology; SCIENCE -- Life Sciences -- Human Anatomy & Physiology; Bioconjugates; Adjuvants, Immunologic; Bioconjugates; Immunohistochemistry -- Methods; Electronic books; Electronic books